Synthesis and the photophysical and biological properties of tricarbonyl Re(i) diimine complexes bound to thiotetrazolato ligands. Issue 15 (20th March 2023) - Stephens, Liam J.; Dallerba, Elena; Kelderman, Jenisi T. A.; Levina, Aviva; Werrett, Melissa V.; Lay, Peter A.; Massi, Massimiliano; Andrews, Philip C.
Abstract : The structure, stability, composition, photochemistry, and biological properties of twelve rhenium tris-carbonyl diamine complexes containing tautomeric thiotetrazolato ligands have been examined for their use as potential bio-imaging agents. Abstract : Twelve Re(i ) tricarbonyl diimine (2, 2′-bipyridine and 1, 10-phenanthroline) complexes with thiotetrazolato ligands have been synthesised and fully characterised. Structural characterisation revealed the capacity of the tetrazolato ligand to bind to the Re(i ) centre through either the S atom or the N atom with crystallography revealing most complexes being bound to the N atom. However, an example where the Re(i ) centre is linked via the S atom has been identified. In solution, the complexes exist as an equilibrating mixture of linkage isomers, as suggested by comparison of their NMR spectra at room temperature and 373 K, as well as 2D exchange spectroscopy. The complexes are photoluminescent in fluid solution at room temperature, with emission either at 625 or 640 nm from the metal-to-ligand charge transfer excited states of triplet multiplicity, which seems to be exclusively dependent on the nature of the diimine ligand. The oxygen-sensitive excited state lifetime decay ranges between 12.5 and 27.5 ns for the complexes bound to 2, 2′-bipyrdine, or between 130.6 and 155.2 ns for those bound to 1.10-phenanthroline. Quantum yields were measured within 0.4 and 1.5%. The complexes were incubated with human lung (A549), brain (T98g), and breast (MDA-MB-231) cancer cells, as well as with normal human skin fibroblasts (HFF-1), revealing low to moderate cytotoxicity, which for some compounds exceeded that of a standard anti-cancer drug, cisplatin. Low cytotoxicity combined with significant cellular uptake and photoluminescence properties provides potential for their use as cellular imaging agents. Furthermore, the complexes were assessed in disc diffusion and broth microdilution assays against methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), Escherichia coli ( E. coli ), and Pseudomonas aeruginosa ( P. aeruginosa ) bacterial strains, which revealed negligible antibacterial activity in the dark or after irradiation.